Andrić and Goya (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2021)
The Yugoslav writer Ivo Andrić spent over two years in Madrid (1928–1930), where he served as viceconsul of the Yugoslav Diplomatic Legation in Spain. His experience of Spain is expressed in some of his works. Spanish themes and motifs appearing in them feature three aspects, one of them associated with the Spanish painter Francisco Goya.Andrić had the opportunity to get well acquainted with the works of Francisco Goya thanks to an extraordinary exhibition of the painter’s works at the Prado Museum on occasion of the centennial of his death (1928). Goya appears in two of Andrić’s works: “Goya” (a biographical essay, 1929) and “Conversation with Goya” (a fictional story, 1935).The study of these two works involves consideration of various issues: generic differences between essay and story (documentary versus fictional), interpretation of Goya’s works (especially The Caprices, The Disasters of War, and drawings) and his poetics, divergence and convergence with essays on Goya written by other contemporary Yugoslav authors (M. Krleža and O. Bihalji Merin).The analysis is especially focused on “Conversation with Goya”, an exceptional story about the creation of Goya as a literary character,  his transformation from historical figure to paradigm of the Artist (shift from biography to philosophy of art), the construction of a (verbal) portrait, the use of epiphany as a metaphor and a narrative resource, the use of interior monologue, the construction of two narrative dimensions (mimetic versus fictional), the analogy with the Portrait of an Artist as a Young Man by J. Joyce, the interaction between “reality” and fiction, and last but not least – the discrete auto-ironic perspective Andrić has woven into this extraordinary narrative.